A systematic literature review of an advisory system - Ain Nadhira, Mohd Taib; Fauziah, Zainuddin; Rahmah, Mokhtar; Kamalia Azma, Kamaruddin; Nadzirah, Ahmad Basri (University of Bahrain, 2024)
The growth of Artificial Intelligence (AI) driven technologies has been proposed as a means to improve the standard of people’s lives. The advent of the advisory system has manifested itself as a significant element in Artificial Intelligence, effectively helping people in various fields. This research presents a systematic literature review of an advisory system. This research initially presents 472 articles by examining the literature between 2015 and 2023. After a meticulous review process, the studies were filtered down to 67 articles for full analysis. This review provides significant contributions to the exploration of advisory systems, specifically in the existing framework of advisory systems, the techniques applied in advisory systems, the domain in which the Artificial Intelligence technique is being applied in the advisory system, and the validation technique used in validating the advisory system. Ultimately, this review contributes to a deeper understanding of an advisory system’s role in Artificial Intelligence and in various domains for optimising an advisory system application.